114k views
3 votes
PLEASE HELP ASAP 25 PTS + BRAIANLIEST TO RIGHT/BEST ANSWER

PLEASE HELP ASAP 25 PTS + BRAIANLIEST TO RIGHT/BEST ANSWER-example-1
User Kedner
by
5.8k points

2 Answers

4 votes

Answer:

f^-1(x) = ±sqrt(x+1)

Explanation:

f(x) = x^2 -1

To find the inverse, exchange x and y and then solve for y

y = x^2 -1

Exchange x and y

x = y^2 -1

Add 1 to each side

x+1 = y^2

Take the square root of each side

±sqrt(x+1) = sqrt(y^2)

±sqrt(x+1) = y

f^-1(x) = ±sqrt(x+1)

User Darkhydro
by
6.5k points
1 vote

Replace f(x) with y:

y = x^2 -1

swap the variables:

x = y^2 -1

Solve for y:

Add 1 to each side:

y^2 = x+1

Take the square root of both sides:

y = √(x+1)

To complete the solution use both the positive and negative values.

f^-1(x) = +/+√(x+1)

The last answer is the right one.

User Jvtech
by
6.2k points